Investigation of the optical properties of unirradiated and irradiated sediments; Journal of Physics: Conference Series; Vol. 1115 : 6th International Congress "Energy Fluxes and Radiation Effects". 18th International Conference on Radiation Physics and Chemistry of Condensed Matter (18th RPC) - Kupchishin A. I. Anatoliy Ivanovich; Niyazov M. N. Maktybek Niyazovich; Lisitsyn V. M. Viktor Mikhailovich; Taipova B. G. Baktygul Gumarovna; Voronova N. A. Nataljya Alekseevna; Abdukhairova A. T. Alchachak Tanyshevna; Khodarina N. N. (2018, 2018)
Title screen